Testing the association of relative growth rate and adaptation to climate across natural ecotypes of Arabidopsis. Issue 2 (8th August 2022) - Fletcher, Leila R.; Scoffoni, Christine; Farrell, Colin; Buckley, Thomas N.; Pellegrini, Matteo; Sack, Lawren
Summary: Ecophysiologists have reported a range of relationships, including intrinsic trade‐offs across and within species between plant relative growth rate in high resource conditions (RGR) vs adaptation to tolerate cold or arid climates, arising from trait‐based mechanisms. Few studies have considered ecotypes within a species, in which the lack of a trade‐off would contribute to a wide species range and resilience to climate change. For 15 ecotypes of Arabidopsis thaliana in a common garden we tested for associations between RGR vs adaptation to cold or dry native climates and assessed hypotheses for its mediation by 15 functional traits. Ecotypes native to warmer, drier climates had higher leaf density, leaf mass per area, root mass fraction, nitrogen per leaf area and carbon isotope ratio, and lower osmotic potential at full turgor. Relative growth rate was statistically independent of the climate of the ecotype native range and of individual functional traits. The decoupling of RGR and cold or drought adaptation in Arabidopsis is consistent with multiple stress resistance and avoidance mechanisms for ecotypic climate adaptation and would contribute to the species' wide geographic range and resilience as the climate changes.